Profiling Fraud, Fraudster, and Victim - Septarina Prita Dania Sofianti; Andriana Andriana; Intan Fauzia Az-zahra (Universitas Hayam Wuruk Perbanas, 2024)
Globally, companies often face occupational fraud, which is considered the most damaging type of fraud for businesses, accounting for five percent of their annual income losses each year. Profiling is one effective technique for preventing and detecting occupational fraud. This process involves creating profiles of both fraud victims and perpetrators. This qualitative research, employing a descriptive study method, aims to analyze trends in victim profiles, types of fraud, and fraudster profiles over the past decade, using data from the Association of Certified Fraud Examiners (ACFE) for the years 2012–2022. The findings indicate that financial statement fraud results in the highest financial losses, despite being the least common type of fraud. Conversely, asset misappropriation is the most frequent type of fraud but results in the lowest financial losses. The most common profile of fraud perpetrators includes the following characteristics: male, aged between 31 and 45, employed in a non-managerial position, holding a bachelor's degree, having worked for one to five years, with no criminal history, and living beyond their means. Additionally, smaller firms are more susceptible to fraud, and organizations in the banking and financial sectors are particularly vulnerable to occupational fraud.